(untitled) (Advances in Applied Biological Research, 2024)
The present study was conducted from July to December, 2021 to find out phylogenetic relationship among different species of pigeons captured from different sites of district Kasur. The live specimens were shifted to the Avian Conservation and Research Center (ACRC), Department of Wildlife and Ecology, UVAS for molecular analysis. All the specimens were morphologically identified via classical taxonomic keys. The blood samples were collected into EDTA tubes by puncturing the brachial vein. Salt extraction was used to isolate DNA from whole blood samples. An agarose gel electrophoresis was used to confirm the DNA’s purity and quantification was done through Nano drop-One. All the DNA samples were Sanger sequences on 13730XL DNA Analyzer from Korea. After trimming bases, the obtained COI fragments were 675 bp. The obtained DNA sequences were submitted to Genbank and accession numbers were obtained (OL774678, OL778850, OL778945 and OL780846). The obtained DNA sequences have shown clear species identification of all the captured specimens. Closely related DNA sequences were downloaded in Blast searches from the NCBI and incorporated in the Neighbour-joining tree. Neighbour-joining tree was constructed based on p-distance using MEGA 10.0. The whole genetic divergence of Columba livia and Columba rupestris was 0.003±0.001 and 0.014±0.004 respectively. It was concluded that more studies related to DNA barcoding should be done to find any new or subspecies from study area.